Temperature-dependent leakage current characteristics of Pr and Mn cosubstituted BiFeO3 thin films - Wu, Di (2011)
Leakage current characteristics of (Bi0.86Pr0.14)(Fe0.95Mn0.05)O3 (BPFMO) thin films are studied at various temperatures from 293 down to 93 K. Space charge limited current and Poole–Frenkel (PF) emission are found to be the dominant mechanism in the low and the high electric fields, respectively. The trap ionization energy at zero-field in BPFMO films is deduced to be around 0.29 eV, which indicates the existence of shallow traps. A negative differential resistivity behavior is observed before the onset of PF emission at 93 K, which is discussed in terms of the competition between electron trapping and field-assisted thermal emission.